DEVELOPING INTERCULTURAL COMPETENCE OF PRE-SERVICE ENGLISH LANGUAGE TEACHERS BASED ON A PLURICULTURAL APPROACH: DEVELOPING INTERCULTURAL COMPETENCE OF PRE-SERVICE ENGLISH LANGUAGE TEACHERS BASED ON A PLURICULTURAL APPROACH - Mamirbaeva, Dina (Журнал иностранных языков и лингвистики, 2025)
In today's globalized environment, English language education is no longer confined to grammatical accuracy or fluency. It encompasses the broader goal of enabling learners to communicate effectively in multicultural settings. Intercultural competence refers to the ability to understand, communicate, and interact effectively with individuals from diverse cultural backgrounds. This competence is particularly vital in educational settings, international business environments, and multicultural societies [1; 41]. Teachers of English as a Foreign Language (EFL) are at the forefront of this transformation, acting as mediators between languages and cultures. Accordingly, the development of intercultural competence has emerged as a core component of teacher training.